Translator status in history: a case of 19th-century diplomatic translators at the British Legation in China - Zhang, Yingying (The Journal of specialised translation, 2023)
This article examines the occupational status of the British and Chinese translators and interpreters who worked in the British Legation in Beijing in the late 19th century. It draws primarily on the official archives of the British Legation and the British Foreign Office. Five status parameters were studied and possible factors behind the observed status manifestations and perceptions were explored. While the British translator-interpreters often had exceptional visibility, recognition and influence at the Legation, they suffered from low official rank and unattractive pay. The Chinese co-translators had lower rank, salaries, visibility and influence, yet their importance and expertise were no less valued in the institution. The Legation translators’ status was shaped by complex interactions between multiple macro, institutional, human and contingent factors, including the stage of Anglo-Chinese encounters, professionalisation level of diplomacy, bureaucratic tradition, material environments, personal contacts and translators’ ethnicity. The findings highlight the complexity of translator status as a multi-faceted and context-dependent construct in real-life settings.